Fibrillar type I collagens enhance platelet-dependent thrombin generation via glycoprotein VI with direct support of α2β1 but not αIIbβ3 integrin - Lecut, Christelle; Feijge, Marion A. H.; Cosemans, Judith M. E. M.; Jandrot-Perrus, Martine; Heemskerk, Johan W. M. (Thrombosis and Haemostasis, 2005)
The role of collagens and collagen receptors was investigated in stimulating platelet-dependent thrombin generation. Fibrillar type-I collagens, including collagen from human heart, were most potent in enhancing thrombin generation, in a way dependent on exposure of phosphatidylserine (PS) at the platelet surface. Soluble, non-fibrillar type-I collagen required pre-activation of integrin α2β1 with Mn2+ for enhancement of thrombin generation. With all preparations, blocking of glycoprotein VI (GPVI) with 9O12 antibody abrogated the collagen-enhanced thrombin generation, regardless of the α2β1 activation state. Blockade of α2β1 alone or antagonism of autocrine thromboxane A2 and ADP were less effective. Blockade of αIIbβ3 with abciximab suppressed thrombin generation in platelet-rich plasma, but this did not abolish the enhancing effect of collagens. The high activity of type-I fibrillar collagens in stimulating GPVI-dependent procoagulant activity was confirmed in whole-blood flow studies, showing that these collagens induced relatively high expression of PS. Together, these results indicate that: i) fibrillar type-I collagen greatly enhances thrombin generation, ii) GPVI-induced platelet activation is principally responsible for the procoagulant activity of fibrillar and non-fibrillar collagens, iii) α2β1 and signaling via autocrine mediators facilitate and amplify this GPVI activity, and iv) αIIbβ3 is not directly involved in the collagen effect.
Keywords: Coagulation; collagen; glycoprotein VI; platelets; thrombin generation